Unity and mission : a study of the concept of unity in ecumenical discussions since 1961 and its influence on the world mission of the church - Saayman, Willem Adriaan (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 1980.